The Theological and Inculturative Values of Lamentation Songs In Good Friday Services - Herman Punda Panda (Sekolah Tinggi Teologi Intheos Surakarta, 2024)
Many Christian communities in Sumba practice a unique tradition of incorporating lamentation songs in regional languages into their Good Friday services. These poignant melodies, born out of the local Christian community, trace their roots to the ngi'o teki tradition—a practice characterized by the expressive mourning of the departed through carefully crafted and emotional words. Despite the fact that such lamentations diverge from the official Good Friday services outlined in the widely accepted Roman Liturgy of the Catholic Church, they play a significant role in the cultural and religious fabric of these communities. This qualitative research aimed to delve into the historical and cultural context of these lament songs, unveil their theological and inculturative values, and discern their specific place within the Good Friday service. The findings of this research underscored the intrinsic theological and inculturative values embedded in lament songs, emphasizing their crucial role in rendering the Good Friday liturgy more resonant and meaningful for the local population.